2022
DOI: 10.1039/d1dt03699h
|View full text |Cite
|
Sign up to set email alerts
|

Solution-processed light-induced multilevel non-volatile wearable memory device based on CsPb2Br5 perovskite

Abstract: Despite of the recent advancements on memory devices, quest for the building materials having low-power consumption is still on with the ultimate focus over durability of system and reliability and...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 20 publications
(7 citation statements)
references
References 49 publications
1
6
0
Order By: Relevance
“…This diffraction peak is due to the phase transformation and degradation of CsPbBr 3 into CsPb 2 Br 5 as a result of moisture incorporation into the crystal lattice. This is consistent with the reported instability of CsPbBr 3 in air and was previously observed in CsPb 2 Br 5 synthesized using different ratios of PbBr 2 and CsBr in water. , The PL spectrum taken after 2 weeks (see Figure b) shows a decreased intensity along with two emission peaks due to the mixture of CsPbBr 3 and CsPb 2 Br 5 . ,, After 8 weeks in air, the PL intensity further decreases and more peaks are observed. As expected, this result again demonstrates the instability of the bulk CsPbBr 3 under ambient conditions.…”
Section: Resultssupporting
confidence: 90%
“…This diffraction peak is due to the phase transformation and degradation of CsPbBr 3 into CsPb 2 Br 5 as a result of moisture incorporation into the crystal lattice. This is consistent with the reported instability of CsPbBr 3 in air and was previously observed in CsPb 2 Br 5 synthesized using different ratios of PbBr 2 and CsBr in water. , The PL spectrum taken after 2 weeks (see Figure b) shows a decreased intensity along with two emission peaks due to the mixture of CsPbBr 3 and CsPb 2 Br 5 . ,, After 8 weeks in air, the PL intensity further decreases and more peaks are observed. As expected, this result again demonstrates the instability of the bulk CsPbBr 3 under ambient conditions.…”
Section: Resultssupporting
confidence: 90%
“…7 Many studies have focused on flexible films to obtain a diversity of luminescent material designs. [8][9][10][11] Due to their adjustable emitting range, high PL quantum yields (PLQYs), high color purity, and easy synthesis, all-inorganic perovskite NCs have aroused great interest. The perovskite NCs have become an outstanding candidate for light-emitting diodes (LEDs), photodetectors, solar cells, and lasers.…”
Section: Introductionmentioning
confidence: 99%
“…The halide perovskites (ABX 3 , X ¼ Cl, Br, I, and their combinations) are among several classes of materials undergoing unprecedented research due to their unique optoelectronic properties that have found enormous utility in next-generation solar cells, photodetectors, LEDs, sensors, memory devices, and lasers. [1][2][3][4][5][6][7][8][9][10][11] Hybrid perovskites with excellent optical absorption, high carrier mobility, long diffusion length, variable bandgap, and high solution processability have resulted in photovoltaic advancements with exceptional power conversion efficiencies. [12][13][14][15][16] Simultaneously, the discovery of intriguing electronic features has led to intense research in the area of energy storage devices like capacitors and batteries.…”
Section: Introductionmentioning
confidence: 99%